Pengaruh Disiplin Kerja Terhadap Kinerja Melalui Motivasi Kerja Karyawan PT XYZ - Ananda Natasya; Ika Korika Swasti (Jurnal Ekonomi Bisnis dan Manajemen, 2026)
This study aims to analyze the effect of work discipline on employee performance, work discipline on work motivation, work motivation on employee performance, and the mediating role of work motivation between work discipline and employee performance at PT XYZ. This research employs a quantitative approach using a census (saturated sampling) method involving all 60 employees of the production and woodworking divisions. Data were collected through questionnaires and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Findings reveal that work discipline does not directly and significantly affect employee performance (H1 rejected). However, work discipline has a positive and significant effect on work motivation (H2 accepted), and work motivation has a positive and significant effect on employee performance (H3 accepted). Furthermore, work motivation serves as a full mediating variable in the relationship between work discipline and employee performance (H4 accepted). These results suggest that companies should not only enforce disciplinary rules but also intensify efforts to strengthen employee work motivation to achieve optimal performance outcomes.